Evidence of impact: Climate-smart agriculture in Africa - Nyasimi, Mary; Amwata, D.; Hove, L.; Kinyangi, James; Wamukoya, George (Technical Centre for Agricultural and Rural Cooperation, 2014)
Agriculture across Africa must undergo a significant transformation to meet the multiple challenges of climate change, food insecurity, malnutrition, poverty and environmental degradation. The case studies described here are just some of the climate-smart agricultural practices that already exist in Africa. This publication aims to inspire farmers, researchers, business leaders, policy makers and NGOs to take up the mantle of climate-smart agriculture and accelerate the transformation of Africa’s agriculture into a more sustainable and profitable sector. French version http://hdl.handle.net/10568/67191